ANALISIS FAKTOR KINERJA KEUANGAN ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA FAKTOR YANG MEMPENGARUHI DI INDONESIA - AJENG PIPIT FITRIANI ; Sutrisno T.Aulia Fuad Rahman (Thesis Akuntansi FEB - UB, 2018)
This research purpose is to test empirically and analyze the influence of zakat, qardh, murabahah, mudharabah, musyarakah, and corporate social responsibility towards financial performance Commercial Bank Syariah in Indonesia in 2012-2016 period of time. The analyzing technique used double linear regression. Research population is Syariah Commercial Bank listed in Financial Service Authority (in Indonesia called OJK) year 2012-2016. The sample taken by using purposive sampling, within the Syariah Commercial Bank criteria that showed the financial report in 2012-2016 period and the number of taken samples is 10 out of 13 Syariah Commercial Bank in Indonesia. The result shows several findings. First, the research result showed that zakat, qardh, and murabahah does not affect the Syariah Commercial Bank financial performance. Second, Increasing on musyarakah financing can improve the financial performance of Syariah Commercial Banks. Increasing on mudharabah and corporate social responsibility activities carried out by banks can reduce financial performance, because mudharabah has various risks one of them is mudharib negligence in running a business, while corporate social responsibility activities are a long-term investment. Key Words: syariah enterprise theory (SET), financial performance, syariah commercial banks, corporate social responsibility